Evolution of Longitudinal Resistance Performance of Granular Ballast Track with Durable Dynamic Reciprocated Changes - Jieling Xiao; Hao Liu; Ping Wang; Ganzhong Liu; Jingmang Xu; Rong Chen (Advances in Materials Science and Engineering)
A full-scale test model with a distinct loading system is developed to analyze the dynamic change process of ballast beds under cyclic longitudinal reciprocated loading. The test analysis methodology accounts for the service performance, longitudinal resistances, and evolution trend of ballast beds under long-term loading. The analysis shows that the ballast resistance-displacement curves under cyclic loading are a set of closed hysteretic curves, indicating obvious energy consumption. In particular, a granular ballast bed is subject to cyclic softening during the cyclic process and the ballast longitudinal resistances degenerate obviously. More particularly, the cyclic softening of a granular ballast bed is dependent on the dynamic disturbance amplitude—the higher the dynamic disturbance amplitude, the more severe the cyclic softening will become. Moreover, this methodology contributes to forming a foundation for an in-depth understanding of the dynamic service performance of ballast CWR tracks and of the stress deformation mechanism of continuously welded rail tracks.